Detection of a Broad Range of Low-Level Major Histocompatibility Complex Class II–Restricted, Hepatitis Delta Virus (HDV)–Specific T-Cell Responses Regardless of Clinical Status. (23rd September 2018) - Landahl, Johanna; Bockmann, Jan Hendrik; Scheurich, Christoph; Ackermann, Christin; Matzat, Verena; Heide, Janna; Nuurei, Tungalag; D'Antonio, Gianluca; von Felden, Johann; Sette, Alessandro; Peine, Sven; Lohse, Ansgar W; et al.
Abstract: Background: This study aimed to comprehensively define the breadth and specificity of the hepatitis delta virus (HDV)–specific T-cell response in patients at different stages of chronic coinfection with hepatitis B virus (HBV). Methods: Following in vitro stimulation with an overlapping set of 21 HDV-specific 20mer peptides and exogenous interleukin 2, HDV-specific CD4 + and CD8 + T-cell responses of 32 HDV-infected patients were analyzed by enzyme-linked immunospot analysis and intracellular cytokine staining for interferon γ production at the single-peptide level. Additionally, HLA-binding studies were performed both in silico and in vitro. Results: We were able to detect ≥1 T-cell response in >50% our patients. Interestingly, there was no significant difference between the breadth of the response in patients positive and those negative for HDV by PCR. HDV-specific T-cell responses focused on 3 distinct HDV-specific epitopes that were each detected in 12%–21% of patients—2 HLA class II–restricted epitopes (amino acids 11–30 and 41–60) and 1 major histocompatibility complex class I–restricted epitope (amino acids 191–210). In in vitro HLA-binding assays, the 2 CD4 + T-cell specificities (amino acids 11–30 and 41–60) showed promiscuous binding to multiple HLA-DR molecules. Conclusions: This comprehensive characterization of HDV T-cell epitopes provides important information that will facilitate further studies of HDV immunopathogenesis.